Effect of copper ferrite (CuFe2O4) in the thermal decomposition of modified nitrotriazolone. Issue 12 (25th May 2022) - Dave, Pragnesh N.; Thakkar, Riddhi; Sirach, Ruksana; Chaturvedi, Shalini
Abstract : The reusable and easily separable nano-copper ferrite has been used to study its excellent catalytic behavior for thermolysis of modified nitrotriazolone (NTO), an insensitive energetic material act as an oxidizer for chemical propulsion systems. Abstract : Nano-crystalline copper ferrite (CuFe2 O4 ) was prepared by a co-precipitation method and physicochemically characterized by powder X-ray diffraction (XRD), Raman, and ultraviolet-visible spectroscopy. Its catalytic effect was studied by the thermal decomposition of nitrotriazolone (NTO, 3-nitro-1, 2, 4-triazol-5-one) and nano-NTO using thermogravimetric analysis-differential scanning calorimetry-differential thermal analysis (TGA-DSC-DTA). XRD showed the amorphous structure of the CuFe2 O4 nanoparticles with the crystallite size found to be between 18 and 29 nm, whereas the nanoparticle size of modified NTO was 10–45 nm. For the purpose of comparison, variations in particle size, absorbance, Raman small shift and kinetics, and differences in the thermal decomposition peak temperature were observed. All samples showed absorbance in the ultraviolet region at 200–400 nm. Kinetic parameters confirmed that the prepared CuFe2 O4 catalyst enhanced the thermolysis of nano-NTO as compared to the pure NTO, nNTO, and NTO + CuFe2 O4 .